UPAYA PEMERINTAH KABUPATEN KAMPAR DALAM MEWUJUDKAN ZERO PENGANGGURAN TAHUN 2013-2014 - Nurul Huda Mohsin; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was motivated by the government of Kampar regency very aggressively to achieve zero unemployment namely Kampar free from unemployment. But the realization condition after four years running from 2011 to 2014 unchanged improved. The unemployment rate in Kampar regency is still very high and even the highest ranks second in Riau. There are two formulation of the problem in this research is "How Kampar regency government's efforts in realizing zero unemployment in 2013-2014 and what are the barriers and obstacles encountered in achieving zero unemployment in 2013-2014". The research is a qualitative descriptive method. Data collected by the author using interview techniques and documentation. The data used are primary data obtained from informants and further research was supported by secondary data obtained from various government agencies associated with this research.The results showed that in the effort to achieve zero unemployment Kampar regency government has issued a policy regarding the use of local labor that local regulation No. 5 of 2009 on employment, but in the implementation of the policy is not going well. Department of Social Welfare and Labor as the leading sector has been carrying out activities that support these policies such as socialization policy, compulsory reporting of vacancies, job canvassing, online job market, as well as job training. For the long term the government seeks to increase the Vocational High School in Kampar regency. Kampar District Government is faced with various obstacles such as the clarity of the policy itself, job seekers public educational background and do not have the skill. In addition to internal factors such as inadequate infrastructure and instructors who have professional work. Lack of jobs and job-seekers which are selective inhibitors also become Kampar regency government.Keywords: Effort, Zero Unemployment, Regional Regulation, Kampar District